Biosynthesis of Crystalline Silver and Gold Nanoparticles by Extremophilic Yeasts - Ana Mourato; Mário Gadanho; Ana R. Lino; Rogério Tenreiro (Bioinorganic Chemistry and Applications)
The biosynthesis of Ag and Au nanoparticles (NPs) was investigated using an extremophilic yeast strain isolated from acid mine drainage in Portugal. Three distinct studies were performed, namely, the growth of yeast strain in presence of metal ions, the use of yeast biomass for the metal nanoparticles synthesis, and of the supernatant obtained after 24-hour incubation of yeast biomass in water. The extremophilic strain under study was able to grow up to an Ag ion concentration of 1.5 mM whereas an increase of Au ion concentration over 0.09 mM caused a strong inhibitory effect. A successful route for the metal NPs synthesis was obtained using the yeast biomass. When the washed yeast cells were in contact with Ag or Au solutions, AgNPs smaller than 20 nm were produced, as for the AuNPs diameter ranged from 30 to 100 nm, as determined through transmission electron microscopy and confirmed by energy-dispersive X-ray spectra. The supernatant-based strategy provided evidence that proteins were released to the medium by the yeasts, which could be responsible for the formation and stabilisation of the Ag NPs, although the involvement of the cell wall seems fundamental for AuNPs synthesis.